Effects of Progressive Resistance Training on Muscle Mass, Muscle Strength, and Physical Function in Elderly Patients with Sarcopenia - Zheng, Yangyang; Li, Lan (International Journal of Public Health and Medical Research, 2025)
This systematic review and meta-analysis evaluates the effects of progressive resistance training (PRT) on muscle mass, muscle strength, and physical function in elderly patients with sarcopenia. Eleven randomized controlled trials involving 316 participants were included. The results indicate that PRT significantly improves grip strength (SMD = 3.22, 95% CI: 2.62–3.82, P < 0.00001), gait speed (SMD = 0.51, 95% CI: 0.27–0.75, P < 0.00001), and skeletal muscle index (SMD = 0.39, 95% CI: 0.07–0.72, P = 0.02). However, PRT did not show significant effects on chair stand time or the Short Physical Performance Battery (SPPB) score. The findings suggest that PRT is a feasible and effective intervention for improving certain aspects of sarcopenia in the elderly, though its impact on comprehensive physical function requires further investigation.